İŞYERİNDE ÇALIŞAN BİR İŞÇİNİN HEPATİT-B HASTALIĞINA YAKALANMASI NEDENİYLE DİĞER İŞÇİLERİN İŞ SÖZLEŞMELERİNİ DERHAL FESİH HAKKI - (:unkn) unknown (My University, 2015)
İş Kanunu'nun 24. maddesinin I. fıkrasının b bendine göre, "İşçinin sürekli olarak yakından ve doğrudan buluşup görüştüğü işveren yahut başka bir işçi bulaşıcı veya işçinin işi ile bağdaşmayan bir hastalığa tutulursa" işçi iş sözleşmesini haklı nedenle derhal feshedebilir. Madde 24/I-b bendinde belirtilen iş sözleşmesinin feshine yol açabilecek hastalığın işçinin "sürekli olarak yakından ve doğrudan buluşup görüştüğü işveren yahut başka bir işçide" gerçekleşmesi gerekirHepatit B hastalığından korunmak için tüm dünyada güvenle ve büyük başarıyla kullanılan hepatit B aşıları vardır. Hepatit B aşısı ile aşılanmış ve kanında yeterli koruyucu antikor oluşmuş kişilere hepatit B mikrobu bulaşsa bile aktif hastalık gelişmemekte ve kişideki hafıza hücreleri nedeniyle kanındaki koruyucu madde düzeyi daha da yükselerek kişi hasta olmaktan korunmaktadır. Yargıtay 9. HD'nin 29.09.2014 tarihli bozma ilamında isabetli olarak belirtildiği gibi, işçilerin hepatit B aşısı yaptırması halinde, işyerinde çalışan başka bir işçiden (hemşireden) hepatit B hastalığı bulaşma ihtimali bulunmamakta olup, bu durumda başka işçideki bulaşıcı hastalık diğer işçiler açısından haklı fesih nedeni oluşturmamaktadır.

According to the Article 24/I-b of Labour Law; if the employer or another employee who is constantly near the employee and with whom he is in direct contact is suffering from an infecting disease or from a disease incompatible with the performance of his duties, the employee is entitled to terminate the employment contract. The disease which can cause the termination as indicated in the Article 24/I-b should be “in the employer or another employee who is constantly near the employee and with whom he is in direct contact.” There are Hepatitis B vaccines that are safely used in the world with great success for being protected from the Hepatitis B disease.Even if the persons who are vaccinated with Hepatitis B vaccines and in whose blood protective antibodies are adequately formed are infected with Hepatitis B, the active disease is not developed and the person is protected from the illness because of the memory cells of the person; which are increasing the protective antibodies in his blood.As it is indicated rightfully in the Supreme Court’s verdict of 29 September 2014; in the case of being vaccinated with Hepatitis B vaccine; there is no possibility to be infected by Hepatitis B from another employee (namely from the nurse). So this situation does not constitute a justified reason for the other employees
THE IMMEDIATE TERMINATION RIGHT OF THE EMPLOYMENT CONTRACT OF THE OTHER EMPLOYEES DUE TO AN EMPLOYEE’S CATCHING HEPATITIS-B WHO IS WORKING IN THE WORKPLACE
Keywords: Hukuk